Quando a lama virou pedra e mandacaru secou... Eu perdi o seu retrato : um estudo semiótico e comparativo dos cacioneiros de Luiz Gonzaga e Adoniran Barbosa - Firmo, Lúcia Maria (2012)
From an experience with students of the courses of Graduation and Specialization in Letras, who were interested in Semiotics and in developed processes in analyses for production and comprehension of texts, it was searched, in Semiotic Theory, subsidies for the exam of meaning of texts in discourse. In this work, which has as corpus selected texts from works of the singers and composers Luiz Gonzaga and Adoniran Barbosa, It was done comparative analyses, in a semiotic perspective, in three segments narrative structures, discursive structures and fundamental structure , having as general objective to find out the ideologic aspects which are similar or different in the discourses. It justifies the choice of these authors the fact of taking a kind of text closer of student's universe constitutes a facilitative element in assimilation of contents of Portuguese Language, as well as the practice of comparative analysis may be developed in the activities of other concerning subjects in the course of Letras. The importance of this research is justified for working a corpus of the repertory of popular Brazilian music and for comparative analyses that characterize themselves as a different work. The methodology was the comparative analysis of the following pairs of texts: Paraíba (Luiz Gonzaga/Humberto Teixeira)/Iracema (Adoniran Barbosa), Cidadão1 1 Music sung by Luiz Gonzaga. (Lúcio Barbosa)/Despejo na Favela (Adoniran Barbosa) e O Xote das Meninas (Zé Dantas/Luiz Gonzaga)/Vila Esperança (Adoniran Barbosa/Marcos César), based on theoric studies which were done in Linguistics and Semiotics and about the authors life and work, with more attention for the used themes in composition of their texts.